Public policies and urban solid waste management in the Municipality of Rafael Fernandes/RN (Research, Society and Development, 2020)
This study aims to analyze the integrated management of urban solid waste in the city of Rafael Fernandes/RN, amidst the limitations and challenges imposed by the National Solid Waste Policy Law - PNRS. Over the years, this city has been observed in growth, both in terms of population and urban space. As a result, Rafael Fernandes incorporates problems experienced by small cities, mainly the large production of solid waste and its inadequate outcome. This reality interferes with the conditions of the environment and the quality of life of the population. The research consisted of a bibliographic review and fieldwork, which allowed the contact of the researcher with this problem. Additionally, it was also characterized as exploratory and descriptive, as it describes aspects of a growing location and its population. The results analyzed revealed several problems, involving economic, environmental and social aspects, such as the improper disposal of solid waste. It is perceived that the challenges are enormous and the actions developed are far from ideal, for the environment and for the population, municipal managers need to develop strategies, and take actions that raise awareness on the part of the population in order to extinguish this great challenge.